2021
DOI: 10.3390/mps4020026
|View full text |Cite
|
Sign up to set email alerts
|

Toxin Removal and Inflammatory State Modulation during Online Hemodiafiltration Using Two Different Dialyzers (TRIAD2 Study)

Abstract: Uremic toxins play a pathological role in atherosclerosis and represent an important risk factor in dialysis patients. Online hemodiafiltration (HDF) has been introduced to improve the clearance of middle- and large-molecular-weight solutes (>500 Da) and has been associated with reduced cardiovascular mortality compared to standard hemodialysis. This non-randomized, open-label observational study will explore the efficacy of two dialyzers currently used for online HDF, a polysulfone-based high-flux membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…During a single session of post-dilution OL-HDF, the mean decrease in serum IL-6 concentration was 2.90 ± 2.83 pg/mL, while the mean IL-6 reduction index was 43.75 ± 15.60%. These results are consistent with the results of other authors, who also showed that post-dilution OL-HDF with an asymmetric triacetate cellulose membrane reduces the concentration of pro-inflammatory mediators in serum [39], [40], [41].…”
Section: Microinflammationsupporting
confidence: 93%
See 3 more Smart Citations
“…During a single session of post-dilution OL-HDF, the mean decrease in serum IL-6 concentration was 2.90 ± 2.83 pg/mL, while the mean IL-6 reduction index was 43.75 ± 15.60%. These results are consistent with the results of other authors, who also showed that post-dilution OL-HDF with an asymmetric triacetate cellulose membrane reduces the concentration of pro-inflammatory mediators in serum [39], [40], [41].…”
Section: Microinflammationsupporting
confidence: 93%
“…The results of clinical studies show that postdilution OL-HDF with asymmetric triacetate cellulose membrane can be used as an alternative in patients with anamnestic data on hypersensitivity reactions to highpermeability polysulfone membranes, as well as in patients with increased risk of bleeding [41], [42], [43], [44]. The composition and structure of the asymmetric triacetate cellulose membrane enable the fulfillment of the criteria for high-volume post-dilution OL-HDF, while the modified cellulose fibers (absence of hydrophilizing agents) reduce the risk of allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, prospective cross over trials with different dialysis treatment modes and different dialyzer types like the one planned by Donati et al are needed to further evaluate to what extend dialyzer properties can reduce the level of oxidative stress [ 27 ].…”
Section: Discussionmentioning
confidence: 99%